A Critical Evaluation of Vitamin D - Basic Overview 2017
DOI: 10.5772/65103
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Physical Activity

Abstract: Vitamin D is synthesized in the skin following exposure to ultraviolet radiation, producing cholecalciferol, while only a small percentage of the circulating vitamin D is of exogenous origin deriving from food. Following two sequential hydroxylations, in the liver and in the kidneys, vitamin D is fully activated. Although its role in bone physiology and calcium homeostasis is well documented, there is emerging evidence that vitamin D exerts a plethora of additional effects on most tissues regulating the muscul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 197 publications
(293 reference statements)
1
7
0
Order By: Relevance
“…[33,34] This might be explained by the decreased exposure of skin to ultraviolet rays due to low outdoor physical activity and consequently decreased synthesis of VD. [35] On the other hand, VDD may be the cause of low physical activity due to associated decline in neuromuscular function including muscular strength, walking speed, balance, jumping and sprinting performance, and aerobic capacity. [36] In contrary to this, Bezuglov et al, 2019 [37] reported that VDI and VDD are highly prevalent in adult soccer players and can exceed 80% even in regions with high insolation although their regular physical activity and suggested daily usage of cholecalciferol in a dose 5000 IU was an effective and well-tolerated treatment for VDI in them.…”
Section: Discussionmentioning
confidence: 99%
“…[33,34] This might be explained by the decreased exposure of skin to ultraviolet rays due to low outdoor physical activity and consequently decreased synthesis of VD. [35] On the other hand, VDD may be the cause of low physical activity due to associated decline in neuromuscular function including muscular strength, walking speed, balance, jumping and sprinting performance, and aerobic capacity. [36] In contrary to this, Bezuglov et al, 2019 [37] reported that VDI and VDD are highly prevalent in adult soccer players and can exceed 80% even in regions with high insolation although their regular physical activity and suggested daily usage of cholecalciferol in a dose 5000 IU was an effective and well-tolerated treatment for VDI in them.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, consistent results showing beneficial effects on the muscular mass and power after vitamin D treatment are missing and are still a matter of debate, as exhaustively summarized elsewhere [22]. In athletic and nonathletic populations, an adequate vitamin D level seems to ameliorate physical performance, likely due to hormone-induced enhancement of exercise capacity and cardiorespiratory fitness; in light of this observation, it would be conceivable to control the vitamin D status whenever physical activity is recommended as a therapeutic approach for CV risk prevention, primary or secondary to other diseases [43][44][45][46]. There is evidence that vitamin D accumulates in skeletal muscle cells, which can take up [25(OH)D] from the bloodstream through the vitamin D binding protein (DBP).…”
Section: Vitamin D Orchestrates Skeletal Muscle Integritymentioning
confidence: 99%
“…The widespread prevalence of vitamin D insufficiency and deficiency among adults and children has acquired the status of a pandemic, prompting the study of its pleiotropic effects on the human body at different physiological stages and tissue and cellular levels [ 1 - 3 ]. Vitamin D deficiency is often combined with cardiovascular diseases, hypertension, metabolic disorders, autoimmune diseases, and cognitive impairments [ 3 - 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D deficiency is believed to occur in people who have been exposed to insufficient sunlight, engage in low levels of physical activity, stay indoors for extended periods, and eat poorly. This is particularly true for adolescents, who spend considerable time in front of the computer and do eat not enough foods rich in vitamin D [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation